The art of Shakespeare's sonnets - Vendler, Helen, 1933- (Belknap Press of Harvard University Press, 1999)
In detailed commentaries on Shakespeare's 154 sonnets, the author reveals previously unperceived imaginative and stylistic features of the poems, pointing out not only new levels of import in particular lines, but also the ways in which the four parts of each sonnet work together to enact emotion and create dynamic effect.